대학생들의 학업성취도 및 학습만족도에 대한 팀 기반 학습 적용의 효과에 관한 연구 - 장우심(Woo-Shim Chang) (한국콘텐츠학회논문지, 2016)
The purpose of this study was investigating effects of TBL (Team-based learning) on the academic achievements and learning satisfaction of university students. This study subjects were 46students in social welfare department. This study surveyed instructor-led classes and orientation of TBL, which is provided from the 1st week to 3rd week. Then, TBL was performed from 4th week to 14th week. The results were found by utilizing questionnaires and interviews through free form technology, which produced effective and measured responses. So academic achievements was improved significantly better than classical explanation teaching. And also learning satisfaction was improved with students' substantial amount, interesting and seamless interaction, active learning and participation, improved presentation technique, and competence in mutual communication. I suggest that TBL should be applied to other subjects. 본 연구는 팀 기반 학습을 활용한 대학전공 수업이 학습자들의 학업성취도와 학습만족도에 미치는 영향에 대해 알아보고자 하였다. 연구대상자는 사회복지학과 학생 46명으로 1~3주차는 강의식 수업과 TBL에 대한 소개를 하였으며 4~14주차까지 팀 기반 학습을 진행하였다. 이후 효과 측정은 설문지 및 인터뷰, 자유기술형 응답 등을 활용하였다. 그 결과, 팀 기반 학습을 통한 학업성취도는 강의식 수업보다 유의미하게 향상되었다. 또한 학습자들은 충실한 학습, 흥미롭고 원활한 상호작용, 능동적인 학습과 참여, 발표력과 의사소통 능력의 향상과 함께 학습만족도 역시 향상된 것을 확인할 수 있었다. 그러므로 향후 팀 기반 학습을 다른 교과목에도 적용해 볼 것을 제안하고자 한다.